FACTORS THAT CAUSE FEELINGS OF LONELINESS IN ADOLESCENTS - Khalilova; Mustafoyeva Dilsuz Zarif qizi (Zeta Repository, 2023)
From the psychological characteristics characteristic of adolescence in this article one is the problem of loneliness in husus, as well as the self-awareness of the individual research on trends and factors affecting it the results were reviewed in hususu.